Ontogeny of Synovial Macrophages and the Roles of Synovial Macrophages From Different Origins in Arthritis - Tu, Jiajie; Hong, Wenming; Guo, Yawei; Zhang, Pengying; Fang, Yilong; Wang, Xinming; Chen, Xiaoyun; Lu, Shanshan; Wei, Wei (Frontiers in Immunology, 2019)
The ontogeny of macrophages in most organ/tissues in human body has been proven. Due to the limited number and inaccessibility of synovial macrophages (SM), the origin of SM has not been illuminated. The objective of this study was designed to investigate the ontogeny of SM and to evaluate the role of SM from different origins in arthritis. SM was isolated from Cxcr1-EGFP mice and C57BL/6 mice by a strigent sorting strategy. Flow cytometry, immunostaining and bone marrow chimera model were used to identify different origins of SM. The comparison of cellular features of SM from different origins were evaluated by the total cell number, in situ proliferation, phagocytosis and expressions of pro-inflammatory and anti-inflammatory genes. In addition, collagen-induced arthritis (CIA) mice and rheumatoid arthritis (RA) patients’ synovium were used to validate the role of SM from different origins in arthritis. We identified two origins of SM, embryonic SMs (ESM) and bone marrow SMs (BMSM). The cellular features of ESM and BMSM were compared. Moreover, ESM and BMSM showed different expression patterns in RA patients’ synovium and during the developmental process of CIA mice. Taken together, these reuslts demonstrated that the SM has two origins, ESM and BMSM. The different cellular property and dynamic expression patterns in RA patient and CIA mice highlight the notion that ESM and BMSM might play differenti role in arthritis.